(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of Box Pass and El Rondo training on improving passing accuracy in futsal extracurricular participants at SMA Negeri 1 Tunjungan, Blora Regency. The method used was an experiment with a two-group pretest-posttest design. The research sample amounted to 40 students who were divided into two groups, each of which was given different treatments for 12 training meetings. The instrument used was the passing accuracy test from Irianto (1995). The paired sample t-test results showed that both training methods significantly improved passing accuracy, with an increase of 15.15% in the El Rondo group and 43.29% in the Box Pass group. The independent sample t-test showed a significant difference between the two groups (p = 0.012), with Box Pass training providing higher results. In conclusion, Box Pass training is more effective than El Rondo in improving passing accuracy in beginner futsal players. This study recommends the application of the Box Pass method in basic futsal technique training programs.